Mindful and resilient?: incremental validity of sense of coherence over mindfulness and Big Five personality factors for quality of life outcomes - Grevenstein, Dennis; Aguilar-Raab, Corina; Blümke, Matthias (Journal of happiness studies, 2018)
Though conceptually distinct, mindfulness and sense of coherence (SOC) are empirically related aspects that promote health and wellbeing. The present research explored uniqueness by investigating criterion validity and incremental validity beyond the Big Five personality traits when predicting psychological distress, life satisfaction, and burnout. N = 1033 participated in a cross-sectional study. We used multiple regression analysis to examine the incremental validity of mindfulness (CHIME) and SOC (SOC-13) for psychological distress (SCL-K-9), life satisfaction (SWLS), and burnout (MBI-GS scales: emotional exhaustion, cynicism, personal accomplishment). Mindfulness and SOC had incremental validity over the Big Five traits. Despite a strong overlap (45% shared variance) between mindfulness and SOC, SOC was always the stronger predictor: psychological distress (β = −.52), life satisfaction (β = .57), emotional exhaustion (β = −.23), cynicism (β = −.40), and personal accomplishment (β = −.30). For psychological distress, life satisfaction, and cynicism, SOC statistically explained almost all the criterion validity of mindfulness. The clinical utility of mindfulness for predicting psychological health appears to be of minor importance relative to SOC, regardless whether meditators or non-meditators, who differed in mindfulness, were analyzed. Western approaches to assessing mindfulness may lack crucial social and existential dimensions.